Can ESG Buffer the Pains of Digital Transformation? Evidence from Chinese Listed Companies - Yanfei Wu (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2025)
Despite the strategic imperative of digitalization, its impact on firm performance remains debated, often showing initial negative effects. Using a panel of 1,543 Shanghai Stock Exchange (SSE) listed firms (2013-2023), we investigate the dynamic relationship between digital transformation (DT) and financial performance. Employing two-way fixed-effects models and path analysis, we uncover dynamic effect: DT negatively impacts financial performance contemporaneously, mediated by increased financing constraints, but yields positive returns in the long run. Crucially, we find that strong Environmental, Social, and Governance (ESG) performance mitigates the negative short-term effects of DT. Robustness checks, including replacement variables, PSM-DID and addressing endogeneity, confirm our findings. This study contributes by reconciling mixed evidence on DT's value, identifying financing constraints as a key mechanism, and demonstrating strong ESG enhances early-stage financial resilience.